Separation of presynaptic Cav2 and Cav1 channel function in synaptic vesicle exo- and endocytosis by the membrane anchored Ca2+ pump PMCA. - Krick, N.; Ryglewski, S.; Pichler, A.; Bikbaev, A.; Götz, T.; Kobler, O.; Heine, M.; Thomas, U.; Duch, C. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Synaptic vesicle (SV) release, recycling, and plastic changes of release probability co-occur side by side within nerve terminals and rely on local Ca2+ signals with different temporal and spatial profiles. The mechanisms that guarantee separate regulation of these vital presynaptic functions during action potential (AP)-triggered presynaptic Ca2+ entry remain unclear. Combining Drosophila genetics with electrophysiology and imaging reveals the localization of two different voltage-gated calcium channels at the presynaptic terminals of glutamatergic neuromuscular synapses (the Drosophila Cav2 homolog, Dmca1A or cacophony, and the Cav1 homolog, Dmca1D) but with spatial and functional separation. Cav2 within active zones is required for AP-triggered neurotransmitter release. By contrast, Cav1 localizes predominantly around active zones and contributes substantially to AP-evoked Ca2+ influx but has a small impact on release. Instead, L-type calcium currents through Cav1 fine-tune short-term plasticity and facilitate SV recycling. Separate control of SV exo- and endocytosis by AP-triggered presynaptic Ca2+ influx through different channels demands efficient measures to protect the neurotransmitter release machinery against Cav1-mediated Ca2+ influx. We show that the plasma membrane Ca2+ ATPase (PMCA) resides in between active zones and isolates Cav2-triggered release from Cav1-mediated dynamic regulation of recycling and short-term plasticity, two processes which Cav2 may also contribute to. As L-type Cav1 channels also localize next to PQ-type Cav2 channels within axon terminals of some central mammalian synapses, we propose that Cav2, Cav1, and PMCA act as a conserved functional triad that enables separate control of SV release and recycling rates in presynaptic terminals.